Faktor Penyebab Mahasiswa UNJ Menjalin Hubungan Friend With Benefit - Irsya Rahma; Martini Martini; Nurul Istiqomah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to obtain data about UNJ students who have Friend With Benefit relationships, the forms of relationships they live in, and the factors that cause them to have Friend With Benefit relationships. To get a clear picture of the forms and factors that cause students to have Friend With Benefit relationships, researchers use a qualitative approach by making in-depth observations so as to produce valid data according to the case studies discussed. Data collection techniques were carried out by structured interviews, non-participant observation, and field notes. The results concluded that UNJ students who establish Friend With Benefit relationships mostly establish relationships in the form of True Friend and Just Sex. The causal factor that most of them use as a reason for doing Friend With Benefit is not wanting to commit.